Effect of seed tuber physiological age on leaf area production of potato cultivars Russet Burbank and Atlantic. Issue 1 (October 2020) - Ridwan, Ifayanti; Lisson, Shaun; Brown, Phil
Abstract: A pot trial was conducted to study the effect of seed tuber physiological age on the leaf growth of two potato cultivars. The study was conducted in a controlled stress free environment in a glasshouse at University of Tasmania Horticultural Research Centre. Seed tubers of two cultivars (Atlantic and Russet Burbank) with different physiological ages were used. The trial was set up as a complete randomized block design with four replicates. Some leaf growth characters were observed including the leaf phenology and production. ANOVA on the observed parameters show a significant difference between the physiological ages of the seed tuber used in the leaf growth characters. Higher node or leaf appearance rate was observed in cv. Russet Burbank (39.5 °Cd per leaf) in the plants from older tubers compared to the younger seed tubers (51.2 °Cd per leaf). On the contrary, no significant differences were found for the leaf senescence rate. Seed tuber ages also affected the size of fully expanded leaves in cv. Russet Burbank but not in Atlantic. More branching was found in the plant established from physiologically older seed tubers.